PENGARUH PEMBERIAN RELAKSASI AUTOGENIK TERHADAP TINGKAT KECEMASAN IBU PRIMIGRAVIDA DI BPM KURNIA KECAMATAN DELI TUA KABUPATEN DELI SERDANG - Andayani Boang Manalu; Nurul Aini Siagian; Mutiara Dwi Yanti; Putri Ayu Yessy Ariescha; Dewi Tiansa Barus; Tetty Junita Purba (Jurnal Doppler, 2021)
Autogenic relaxation is one technique that originates from oneself in the form of words or short sentences that can make the mind calm. Autogenic relaxation is done by imagining oneself in a state of peace and calm, focusing on breathing regulation and heart rate thereby reducing physiological tension in primigravida mothers. Maternal death and illness is still a serious health problem in developing countries. According to the 2012 Indonesian Nursing Diagnosis Standards Report (SDKI), it is explained that in 1990 and 2015 the global maternal mortality ratio decreased by 44% to around 216 deaths per 100,000 live births, not reaching the MDGs and far from the target of 70 maternal deaths per 100,000 live births set in agenda 2030. The purpose of the research is to find out the effect of giving autogenic relaxation to the anxiety level of primigravida mothers in (Independent Practice Midwife) BPM Kurnia Deli Tua. The method used in this study is the Pre and post experimental methods. The sample in this study was trimester III primigravida pregnant women who experienced anxiety as many as 20 respondents in (Independent Practice Midwife) BPM Kurnia Delitua. Effect of Autogenic Relaxation on the Anxiety Level of Primigravida at (Independent Practice Midwife) BPM Kurnia Deli Tua District Deli Serdang Regency.